FROM STAGNATION TO THE DEVELOPMENT OF THE RUSSIAN INDUSTRY: WAYS TO IMPROVE MANAGEMENT PRACTICES AND REGULATION - G. S. NIKITIN (Real Economics Publishing House, 2017)
The Article is dedicated to research of the ways to achieve Russia’s strategic goals in the sphere of industrial development under the conditions when import substitution has become one of the main governmental policy trends over the recent years. It is shown that the industrial policy should be underpinned by the project management in order to ensure sustainable development of the key sector of the national economy. Systematized are priority methods of long-term support of industrial enterprises aimed at enhancing the competitiveness of domestic products.